2009
DOI: 10.6026/97320630003440
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of amyloid-beta, adenine nucleotide translocase and cyclophilin-D interaction in mitochondrial dysfunction of Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a common neurodegenerative disease characterized by both extra- as well as intracellular deposition of amyloid beta peptides (Aβ). The accumulation of Aβ in mitochondria is associated with mitochondrial dysfunction and oxidative stress in AD. Recent evidences suggest the involvement of Aβ interaction with mitochondrial proteins such as cyclophilin-D (CypD) in oxidative stress, mitochondrial permeability transition (MPT) and Alzheimer's associated neurodegeneration. The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 17 publications
0
41
0
Order By: Relevance
“…A ␤ is also thought to interact with the mitochondrial membrane. A recent study of interactions between A ␤ and proteins of the membrane permeability transition pore (MPTP) suggested that the interaction between A ␤ and adenine nucleotide translocase is stronger than that between A ␤ and cyclophilin-D [15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A ␤ is also thought to interact with the mitochondrial membrane. A recent study of interactions between A ␤ and proteins of the membrane permeability transition pore (MPTP) suggested that the interaction between A ␤ and adenine nucleotide translocase is stronger than that between A ␤ and cyclophilin-D [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Its interaction with several membrane proteins such as one involved in the MPTP may increase the permeability of mitochondrial membranes [15] . Indeed, we found that the morphology of the mitochondrial membrane was altered at the highest dose of A ␤ 1-42 used (10 M ).…”
Section: Discussionmentioning
confidence: 99%
“…A direct interaction between ANT and Aβ was firstly predicted in a computational simulation and later described using an in vitro assay. In that study Aβ 1-42 fibrils were shown to inhibit ANT1 mediated ADP/ATP exchange in a noncompetitive manner [35,47]. However, the consequences of such an interaction remain elusive as well as characterising the role of ANT in mPT and cell death.…”
Section: Adenine Nucleotide Translocase (Ant)mentioning
confidence: 96%
“…The binding between CypD and Aβ was also studied using computational simulations [35]. It was suggested that CypD mediated Aβ toxicity could be driven in two ways, indirectly by elevated ROS levels caused by Aβ accumulation inside mitochondria and directly, specifically via the CypD-Aβ interaction [31].…”
Section: Cyclophilin D (Cypd)mentioning
confidence: 99%
“…This potential independent pharmacological target of huperzine A on mitochondria may further interpret the anti-oxidative stress [30][31][32][33][34][35][36] and anti-apoptotic effects [30,31,[37][38][39] shown by huperzine A administration in various in vivo and in vitro models (Figure 1). Interestingly, several lines of evidence suggest that Aβ directly interacts with several proteins on and inside mitochondria [40] : Aβ could import into mitochondria through a pore formed by the outer membrane (TOM40) and the inner membrane (TIM22) [41] ; Aβ could also interact with mitochondrial proteins from the membrane permeability transition pore (MPTP) [42] , which may in turn affect the mitochondrial membrane potential; Aβ was also reported to bind with β-amyloid binding alcohol dehydrogenase (ABAD) upon entering into mitochondria and leading to mitochondrial dysfunction [43,44] . Although the precise molecular target of huperzine A on Aβ-induced mitochondrial dysfunction remains to be clarified, whether and how huperzine A affects above mentioned Aβ-mitochondrion interactions could be a very promising future project.…”
Section: Multifaceted Pharmacological Effects Of Huperzine A: Cholinementioning
confidence: 99%